2021
DOI: 10.21608/bfsa.2021.207182
|View full text |Cite
|
Sign up to set email alerts
|

Production and Application of Natural Food Pigments by Monascus Ruber Using Potato Chips Manufacturing Wastes

Abstract: This work was established for using potato chips manufacturing wastes as a substrate for the production of food colorant pigments by Monascus ruber Went AUMC 5705, then it was utilized individually for coloring some food products (drops sweets). The effects of different environmental and nutritional factors were studied in solid state fermentation (SSF). The maximum concentrations of red, orange, and yellow pigments produced by M. ruber were 147.3, 179.6 and 221.7 U/g of dry fermented materials, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…These results are in agreement with previous investigators who reported that food products gain more intense and stable color and improved organoleptic characteristics when M. purpureus pigments were used (Hamano and Kilikian, 2006 and Mal'a et al, 2010 ; Gomah et al, 2017 ; Abdel-Raheam et al, 2019 , 2021 ; Darwesh et al, 2020 ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in agreement with previous investigators who reported that food products gain more intense and stable color and improved organoleptic characteristics when M. purpureus pigments were used (Hamano and Kilikian, 2006 and Mal'a et al, 2010 ; Gomah et al, 2017 ; Abdel-Raheam et al, 2019 , 2021 ; Darwesh et al, 2020 ).…”
Section: Resultssupporting
confidence: 93%
“…Also, starch is the main ingredient in rice, which is usually the major carbon source for Monascus growth and pigment production (Patakova, 2013 ; Chen et al, 2015 ). Abdel-Raheam et al ( 2021 ) used potato chips manufacturing wastes as a suitable substrate for the production of pigment by Monascus ruber Went AUMC 5705 on solid-state fermentation. It was reported that the addition of a C source of 50 g/L can increase the growth rate of molds and increase the synthesis of pigment compounds, cell biomass, and ethanol production (Jones, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As referred to by Sumathi et al [ 59 ], there is a positive correlation between initial inoculum concentration and fermentation byproducts, which resulted in accelerating the production process by reducing the generation time. Similarly, Abdel-Raheam et al [ 60 ] found that the production of yellow, red and orange pigments by Monascus ruber was improved upon increasing the inoculum size to 81 × 10 4 (spores/mL), elucidating that too little inoculum led to insufficient biomass and thereafter lower productivity of metabolites, while higher inoculum concentration generated excessive biomass which is considered an essential precursor for pigment formation, which harmonized with the results of the current study. Generally, the statistical methods of optimization succeeded in improving the carotenoids content of V. halodenitrificans DASH by 2.12-fold when compared to the basal medium.…”
Section: Discussionsupporting
confidence: 87%